(untitled) (Global Journal of Human-Social Science, 2023)
Climate change is a topic that has been gaining importance in global discussions In addition to industries automobiles release greenhouse gases GHG into the atmosphere that act directly on the increase of the greenhouse effect and consequently on the increase in the temperature of the globe which requires measures to minimize their effects on the atmosphere The island of Fernando de Noronha has been used as a model for the implementation of electric mobility Law n 16 810 2020 establishes that until 2030 combustion cars will no longer be allowed to enter the island being replaced by electric cars Solar electric mobility has been gradually taking place in this territory and with conflicts on the part of those interested who use vehicles as a means of subsistence on the island This research aimed to analyze how environmental governance was carried out in the process of inserting electric mobility on the island of Fernando de Noronha PE through bibliographical and documentary research interviews and observation In view of the results it was observed in the environmental governance of the electric mobility insertion process that only three principles of environmental governance were identified within this territory decentralization transparency and security leaving the other principles behind